Comparison measurements of tar content in gasification systems between an online method and the tar protocol. (April 2018) - Gredinger, A.; Spörl, R.; Scheffknecht, G.
Abstract: One of the major obstacles for the application of biomass gasification systems is the relatively high tar content of the producer gas that can inhibit its use in engines or turbines or in further processes like methanation or conversion to other secondary fuels or chemicals. Moreover, tars are difficult to define and also because of the different attempts to do so remains the determination of its content challenging. Nowadays conventional wet chemical and other standard methods for the determination of tars are very time consuming and do not allow continuous online monitoring of the gas quality. Furthermore, the execution by different users can affect the results. One approach to avoid these disadvantages is an automatic system that monitors the tar concentration in the producer gas online during the gasification process. Such an automatic system was developed at IFK in the past with the goal of commercialization and moreover better comparability of the results from tar measuring. To show its accuracy and advantages over standard methods, comparative measurements with the standard method DIN CEN/TS 15439 at an electrically heated lab scale gasifier at different settings have been performed at IFK over several hours. Then, the results of both measurement techniques were compared to each other. The results show a stable operation of the gasifier and therefore also the tar production and its fast detection with the online system. Furthermore, the comparison of the results from both measurement techniques shows good agreement. A satisfying validation of the online method could be conducted. Highlights: An online method for tar concentrations in producer gases from gasification is presented. Comparative tar measurements with the online device and the standard method were conducted. The results show high sensitive online tar detection by the device over several hours. The comparative measurements of both methods are in good agreement. Additional information about the gasification behaviour can be seen while using the online device.